Tiktok as a Microlearning Platform for Improving Vocabulary Mastery and Student Engagement at State Islamic Senior High School - Nahdah Alfiani Rahman; Nanning Nanning; Ambo Dalle; Nur Asiza (Journal of English Language and Education, 2026)
The rapid development of digital technology has encouraged the integration of innovative and interactive media into English language learning. However, vocabulary mastery and student engagement remain relatively low among Grade XI Social Science students at MAN 1 Soppeng. This study aims to investigate the effectiveness of TikTok as a microlearning platform in improving students’ English vocabulary mastery and learning engagement. A quantitative approach employing a pre-experimental one-group pre-test–post-test design was used. The participants consisted of two Grade XI Social Science classes selected through purposive sampling. Data were collected using vocabulary tests and student engagement questionnaires, then analyzed through descriptive statistics, paired-sample *t*-tests, and percentage analysis. The findings are expected to demonstrate that TikTok-based microlearning significantly enhances students’ vocabulary mastery while increasing their active participation and engagement in English learning. By presenting vocabulary through short, interactive, and engaging videos, TikTok offers meaningful learning experiences that encourage continuous practice beyond the classroom. This study is expected to provide practical insights for English teachers seeking to integrate social media into technology-enhanced vocabulary instruction and promote more engaging, student-centered EFL learning environments.